Simulation based evaluation of large scale waste heat utilization in urban district heating networks: Optimized integration and operation of a seasonal storage. (15th September 2018) - Köfinger, M.; Schmidt, R.R.; Basciotti, D.; Terreros, O.; Baldvinsson, I.; Mayrhofer, J.; Moser, S.; Tichler, R.; Pauli, H.
Abstract: The integration of renewable heat sources and industrial waste heat in urban district heating (DH) networks is essential for a sustainable and low-carbon heat supply and therefore a key element for a future prove energy system. Achieving this integration requires the investigation of different technical and infrastructural options, as well as economic analyses for improved implementation. In the city of Linz (Austria), the existing industry exhibits significant unused waste heat potentials which could be integrated into the existing urban DH system, however, a seasonal storage is required due to the competition with an existing waste incineration plant. This paper shows, that a strategic operation of the seasonal storage could increase the number of charging cycles and thereby increase significantly the revenues of the system. This is mainly due to the combined utilization of the storage in a seasonal approach to shift the waste heat from summer to the winter period and as a short term buffer. Thus, the profits from actively participating on the electricity market with the existing combined heat and power (CHP) plants are increased. Highlights: Analyses of the district heating network of the city of Linz. Simulation study of the optimized integration of waste heat using a seasonal storage. Optimization of the charging strategies allows up to 4.4 full load cycles of the storage. Assessment of different scenarios with regards to network temperatures and modifications.